Genetic complexity in the marine environment: Population genomics of saithe (Pollachius virens), Greenland halibut (Reinhardtius hippoglossoides), beaked and golden redfish (Sebastes mentella and S. norvegicus) in the North Atlantic - Saha, Atal (UiT The Arctic University of Norway, 2016)
The papers of this thesis are not available in Munin. Paper I. Saha A et al.: Seascape genetics of saithe (Pollachius virens) across the North Atlantic using single nucleotide polymorphisms. Available in ICES Journal of Marine Science (2015), 72(9), 2732–2741 Paper II. Westgaard J-I, Saha A et al.: SNP markers from RAD sequences reveal management relevant genetic patterns in Greenland halibut (Reinhardtius hippoglossoides). (Manuscript). Paper III. Saha A et al.: Geographic extent of introgression in Sebastes mentella and its effect on genetic population structure. (Manuscript). Paper IV. Saha A et al.: Cryptic Sebastes norvegicus species in Greenland waters revealed by microsatellites. (Manuscript). In this work, I investigated genetic complexity in four commercially exploited species from the North Atlantic: saithe (Pollachius virens L.), Greenland halibut (Reinhardtius hippoglossoides), and beaked and golden redfish (Sebastes mentella and S. norvegicus). The results were used 1) to assess the consistency between current management units and units identified by results based on genetic data for each species, and 2) to assess the efficiency of SNP data compared to conventional markers in studying population genomics. Panels of nuclear genomic markers, including single nucleotide polymorphisms (SNPs) and microsatellites, derived from modern genomic approaches, and data on species life history traits, were analyzed to explore genetic complexity within these highly migratory and continuously distributed species. The investigation reveals biologically distinct populations within each of these species. Four genetic clusters of saithe and two clusters of Greenland halibut were found in the North Atlantic. For beaked redfish, results using both the genome-wide SNP and microsatellite data supported one group (‘shallow’) throughout the North Atlantic and a second group (‘deep’) in the central North Atlantic and Canadian waters. A localized group (‘slope’) of beaked redfish was identified in Greenland and Icelandic ...